Inflation Targeting: El Proceso de Reducción de La Inflación en Colombia. (2019)
Inflation targeting is a monetary policy rule which aims to diminish inflation and keep it at stable low levels. This rule has been successfully implemented by many countries among which is Colombia. After twenty-five years of moderate inflation, Colombia has managed to keep inflation at a one digit level since 1999, reducing uncertainty and increasing the credibility of the Central Bank. This paper describes the main characteristics of the inflation targeting rule, its process of implementation in Colombia and the importance of providing adequate information about the seasonal forecast in order to achieve the aimed inflation target.